An efficient network selection algorithms in next-generation heterogeneous wireless networks. (2017) - Bhute, Harsha Avinash; Karde, P.P.; Thakare, V.M.
In the next-generation heterogeneous wireless networks, it is obligatory to consider the integration of various networks for providing the seamless connectivity to the mobile node roaming. While providing the seamless connectivity, a suitable network to choose from the given set of networks is the crucial issue. During vertical handoff, it is required to select the best network not only according to user preference but also the application, network and terminal contexts. The network selection algorithm plays a very important role in ensuring quality of service and seamless connectivity in such networks. Network selection in heterogeneous wireless networks has been widely studied by using various mathematical models, in which multiple attribute decision-making is one of the most popular models. This paper surveys the different network selection techniques available in the literature and explains a method for network selection which takes into consideration of multiple decision-making criteria for selecting the optimal network.